USING QUIZZIZ APP TO CREATE AN ACTIVE CLASSROOM IN MATHEMATICS LEARNING IN ELEMENTARY SCHOOL - Vina Tamarin; Andi Prastowo (JP (Jurnal Pendidikan))
This research aims to find out what the learning conditions are when using the Quizizz application for Mathematics learning in elementary school. The scope of this research focuses on students and teachers. This research uses a qualitative approach, qualitative data in the form of information from interviews and observations made using qualitative data collection techniques including: Interviews and Documentation. As for data collection techniques for interview data, researchers describe the interview results in the form of descriptions. Researchers use data analysis techniques using the Milles and Huberman theory, namely data condensation, data presentation, and data conclusions. The location of this research was carried out at an elementary school in Yogyakarta, involving one teacher as a resource person. There are two factors that influence learning, namely from within oneself and from outside oneself. From outside, in the form of learning media used, one of which is the Quizizz application. The Quizizz application is a web tool that contains interactive quizzes containing educational content presented in an attractive appearance. Learning mathematics is abstract learning so it requires media to clarify the intended symbols or numbers, so the Quizizz application can help make learning mathematics easier with various interesting features.